2017
DOI: 10.1016/j.dsr2.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Controls of primary production in two phytoplankton blooms in the Antarctic Circumpolar Current

Abstract: The Antarctic Circumpolar Current has a high potential for primary production and carbon sequestration through the biological pump. In the current study, two large-scale blooms observed in 2012 during a cruise with R.V. Polarstern were investigated with respect to phytoplankton standing stocks, primary productivity and nutrient budgets. While net primary productivity was similar in both blooms, chlorophyll a –specific photosynthesis was more efficient in the bloom closer to the island of South Georgia (39 °W, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 80 publications
(116 reference statements)
4
50
0
Order By: Relevance
“…Hence, the fluxes were high and quite similar over the entire study area, despite the differences observed in Chl-a SW inventories (see Section 3.5) and production rates (Hoppe et al, 2017). However, satellite images show widespread high Chl-a concentrations in January 2012 (data not shown).…”
Section: Results and Comparison With Other Studiesmentioning
confidence: 92%
See 4 more Smart Citations
“…Hence, the fluxes were high and quite similar over the entire study area, despite the differences observed in Chl-a SW inventories (see Section 3.5) and production rates (Hoppe et al, 2017). However, satellite images show widespread high Chl-a concentrations in January 2012 (data not shown).…”
Section: Results and Comparison With Other Studiesmentioning
confidence: 92%
“…comm.). Concentrations of dissolved iron (o0.2 μm) were on average 0.12 70.03 nM within the top 100 m of the water column (Hoppe et al, 2017), suggesting that dissolved iron was already depleted by phytoplankton activity during our sampling.…”
Section: Study Areamentioning
confidence: 94%
See 3 more Smart Citations